Electromagnetic activation moisture reaction type solid adhesive

Through the development of electromagnetically activated moisture-reactive solid adhesive, the hydrogen bond crystal structure is interrupted by electromagnetic polarization active agent, and the safety hazards and cumbersome use caused by the need for solvent storage of existing adhesives are solved, and the adhesion effect is achieved with safe, energy-saving and force-saving.

CN119709083APending Publication Date: 2025-03-28RAYA CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311246793.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing adhesives need to be exposed to solvents when used, which leads to safety risks and is cumbersome to use, which consumes manpower and energy.

Method used

An electromagnetically activated moisture-reactive solid adhesive is developed. The adhesive is used to break the hydrogen bond crystal structure by a combination of prepolymers, adhesive enhancers, additives, fillers and electromagnetic polarization active agents, so that the adhesive is liquefied and adhered to the adhesive.

Benefits of technology

The adhesive does not require solvent storage, reduces safety risks, simplifies usage processes, reduces labor and energy consumption, and improves productivity and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709083A_ABST
    Figure CN119709083A_ABST
Patent Text Reader

Abstract

The invention discloses an electromagnetic activation moisture reaction type solid adhesive, which is prepared by the following steps: (1) mixing and heating a prepolymer, a tackifier, an auxiliary agent, a filler and one or more formulas, and drying and dehydrating to obtain a prepolymerized combined solution; (2) cooling the pre-polymerized combined liquid to 70 DEG C or below, adding an electromagnetic polarization active agent, uniformly mixing, adding a diisocyanate curing agent, heating, and carrying out high-molecular polymerization reaction on the pre-polymerized combined liquid; (3) adding a catalyst to accelerate polymerization reaction; (4) in a vacuum environment, nitrogen in the reaction chamber is pumped out, bubbles are removed from a polymerization reaction product, and a solid adhesive is obtained; and (5) unloading the material into a nitrogen protection aluminum foil package and sealing to obtain a commodity. The charged structure of the electromagnetic polarization active agent is quickly concentrated and dispersed by quickly changing the positive electric field and the negative electric field, so that the hydrogen bond crystal structure of the moisture reaction type solid adhesive is broken, and the moisture reaction type solid adhesive is liquefied to achieve adhesion. The adhesive is safe, energy-saving and lower in production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adhesive, in particular to an electromagnetically activated moisture-reactive solid adhesive. Background Art

[0002] Adhesive, in simple terms, is a substance that can make two interfaces stick to each other. It has a wide range of uses and types, and has multiple functions. It can be applied to the production of tapes for people's use. Tapes are absolutely convenient and easy-to-use daily necessities. They can be pasted immediately and can be used on a variety of objects with different uses and shapes, such as LCD TVs, mobile phones, and automobiles. In automotive parts, due to the need for long-term stability, the adhesive must have sufficient strength; the protection of mobile phone screens must be easy to peel off without leaving residual adhesive; polarizing films must use transparent and weather-resistant adhesives; the interior of the vehicle must use adhesives with low VOC (volatile organic compounds). For example, adhesives that can be used in silicon wafer and ceramic processes can maintain a certain strength under normal circumstances, but their strength will be weakened after overheating or exposure to ultraviolet rays.

[0003] There are different types of adhesives, depending on their uses, including rubber adhesives, acrylic adhesives, and silicone adhesives, which are described as follows:

[0004] A. Rubber adhesive: Made from natural rubber, but natural rubber itself has low adhesion, so some kind of tackifier is generally added to allow the rubber adhesive to stick to various objects. It is also used for packaging tape.

[0005] B. Acrylic adhesive: Acrylic monomers can be used for copolymerization to synthesize multifunctional acrylic polymers, which are used as adhesives. Due to their excellent transparency, weather resistance, heat resistance and solvent resistance, they can be widely used in the fields of liquid crystal panels, mobile phones and automotive products. However, when using them, the temperature, durability and heat resistance of the adhesive at the best adhesion, as well as the copolymerization of acrylic monomers must be considered.

[0006] C. Silicone adhesive: Silicone has excellent resistance to extreme heat and cold environments, and has a wide operating temperature range. However, because silicone itself has low adhesion, silicone resin is used as a tackifier, and the required adhesive properties can be obtained by changing the structural ratio of silicone and silicone resin. Cross-linking agents such as benzoyl peroxide can also be used to produce cross-linking effects, thereby improving its heat resistance.

[0007] D. Polyurethane adhesive: This type of adhesive has excellent removability, so it is mostly used in protective films and lint removal equipment.

[0008] The reason why adhesives can interact with the adhered object is mainly because most adhesives are high molecular substances. Not only can the molecules themselves be linked into a solid structure, but they can also be bonded to other substances by chemical chains or mechanical forces. The most basic source of adhesive force is the attraction (bonding) between molecules, such as hydrogen bonding, and the van der Waals force (non-directional, unsaturated interaction force between molecules or atoms) that any adhesive will produce. However, the action distance of molecular forces is usually very small. In order to generate more molecular forces, adhesives are generally in liquid form, using their fluidity to fill the holes on the surface of the adhered object and increase the close contact area.

[0009] The glue that is very common in our industry is mainly composed of polyvinyl alcohol (DVA) and borax. Polyvinyl alcohol is a water-soluble plastic. When borax is added, the boron atoms and oxygen atoms will string the polyvinyl alcohol molecules together, forming a viscous liquid, which is the glue. It will slowly solidify in the air and interlock with the uneven surfaces of the object, allowing the object to resist the external force that wants to separate the two. This is the principle of mechanical interlocking.

[0010] There are many ways to solidify adhesives. The most common one is hot melt adhesive, which melts into a liquid and becomes fluid at high temperatures (65-180°C). After cooling, it solidifies and becomes sticky. Some adhesives solidify when the solvent evaporates and dries.

[0011] In addition to physical curing, there is also curing through chemical reactions. For example, the main component of three-second glue is cyanoacrylate, which will quickly polymerize with water vapor in the air at room temperature and harden into a strong adhesive within seconds. AB glue, which has strong adhesion after drying, is also an example. After mixing the two liquid glues A and B, the two agents will react with each other to form a polymer and solidify.

[0012] After curing, the adhesive can not only generate mechanical force with the adherend, but also strengthen its own structure, because during the curing process, some adhesives evaporate the solvent, making the adhesive molecules closer to each other, thus generating more molecular forces. In addition, some adhesive molecules will entangle with each other, making the objects more firmly bonded, and super glue belongs to this type of adhesive.

[0013] From the above description, we can see that the basic bonding method of adhesives is to first use liquid to moisten the surface of an object, and then solidify it to lock with the object to achieve a tight bond.

[0014] However, the strong glue in adhesives is preserved by solvents. Solvents and solutes can be roughly divided into polar (hydrophilic) and non-polar (hydrophobic). The polarity of the solvent determines the substances it can dissolve and other solvents or liquid substances that can be mixed with each other. Therefore, polar substances dissolve best in polar solvents. This is the principle of like dissolves like. For example, inorganic salts and sugars such as salt and sucrose are highly polar substances and can only be dissolved in highly polar solvents such as water; and strong non-polar substances such as oils, resins, and waxes can only be dissolved in very non-polar organic solvents such as hexane, and polar and non-polar solvents cannot be mixed and dissolved with each other. Polar solvents can be further divided into polar protic solvents and polar aprotic solvents.

[0015] As mentioned above, general adhesives, especially those used in industry, use non-polar solvents, among which the more well-known ones are hexane (CH3-CH2-CH2-CH2-CH3), benzene (C6H6), toluene (C6H5-CH3), diethyl ether (CH3-CH2-O-CH2-CH3), chloroform (CHCl3), etc. However, in actual applications, the industry still takes into account the boiling point (including melting point), polarity, density, price, and even toxicity and safety of the solvent.

[0016] However, non-polar solvents, themselves or in the reactants after the reaction, contain substances that are toxic to the human body, such as benzene. When inhaled into the human body or in contact with the skin, it can cause benzene poisoning, which can cause headaches, nausea, vomiting, coma, convulsions, etc., and even cause central nervous system paralysis and death. Benzene is also a Group I carcinogen recognized by the International Agency for Research on Cancer (IARC), which can damage the bone marrow, reduce the number of red blood cells, white blood cells, and platelets, and cause chromosome aberrations, leading to leukemia! Therefore, in industry, the above-mentioned adhesives generally have the need and urgency to be improved.

[0017] In view of the above-mentioned major deficiencies of the commonly used adhesives, the inventors came up with the idea of ​​innovating them. After years of research, experiments, reviews, revisions, and further experiments, the electromagnetically activated moisture-reactive solid adhesive of the present invention was finally produced. Summary of the invention

[0018] Therefore, the purpose of the present invention is to provide an electromagnetically activated moisture-reactive solid adhesive that does not utilize solvents for preservation. Thus, it overcomes the situation in which conventional adhesives need to come into contact with solvents during use, which causes danger. This is a main purpose of the present invention.

[0019] The electromagnetically activated moisture-reactive solid adhesive of the present invention does not require complicated procedures when used, especially in industrial use, as with general adhesives. The manpower required can be greatly reduced, thereby achieving the effect of saving manpower expenditure, which is the second purpose of the present invention.

[0020] The electromagnetically activated moisture-reactive solid adhesive of the present invention does not require complicated procedures when used, especially in industrial applications, as with conventional adhesives. This can greatly reduce manpower and save energy consumed during operations, providing a smooth path in the current global energy crunch, which is another purpose of the present invention.

[0021] The electromagnetically activated moisture-reactive solid adhesive of the present invention can greatly reduce the process and manpower, and the working space can be greatly reduced, which is another purpose of the present invention.

[0022] The electromagnetically activated moisture-reactive solid adhesive of the present invention achieves the utilization effect with a simpler process and method. In addition to greatly reducing the manpower, the operating equipment can also be greatly improved, with higher efficiency and lower production cost. This is another purpose of the present invention.

[0023] An electromagnetically activated moisture-reactive solid adhesive, the manufacturing method of which comprises the following steps:

[0024] (1) mixing 10-95% of a prepolymer, 1-30% of a tackifier, 0.01-10% of an auxiliary, and 1-30% of a filler, or one or more formulations, heating the mixture to 100° C. to 150° C., and drying and dehydrating the mixture under a vacuum of 650 to 760 mmHg for 30 minutes to 4 hours to obtain a prepolymer composition liquid;

[0025] (2) cooling the obtained prepolymer combination liquid to below 70° C., adding an electromagnetic polarization activator (EMPA), mixing evenly under a nitrogen atmosphere, slowly adding a diisocyanate curing agent (Diisocyanate) under a nitrogen atmosphere, heating to 80-150° C., allowing the prepolymer mixture to undergo a polymer polymerization reaction for 1.5-4 hours, and controlling the terminal isocyanate content to be 0.1-25%;

[0026] (3) adding a catalyst under the nitrogen atmosphere to accelerate the polymerization reaction;

[0027] (4) In a vacuum environment of 650-760 mmHg, the nitrogen in the reaction chamber is evacuated to remove bubbles from the polymerization product to obtain a solid adhesive;

[0028] (5) Unload the material into a nitrogen-protected aluminum foil package and seal it to obtain the product;

[0029] The method for producing the electromagnetic polarization active agent comprises the following steps:

[0030] (1) dissolving one or more of a silane coupling agent and a resistance adjusting agent in acetone, butanone, toluene, ethanol, ethyl acetate or dimethylacetamide to obtain a resistance adjusting agent solution having a solid content of (0.1-30%);

[0031] (2) Pour the required amount of the carrier into the above-mentioned coupling agent and resistance adjusting agent solution and mix and stir for 2-5 hours to make the surface of the carrier undergo organic and inorganic coupling grafting modification and adjust the trace resistance of the carrier surface to 1 mΩ·cm~1 GΩ·cm;

[0032] (3) vacuum drying the solution to completely evaporate the solvent, leaving a solid powder product of the organic molecule-coated carrier;

[0033] (4) The solid powder product is passed through a fluidized bed dryer and a high-voltage electron beam gun to make the surface of the solid powder of the organic molecule-coated carrier electrostatically charged, thereby obtaining an electromagnetically polarized active agent product.

[0034] As for the electromagnetically activated moisture-reactive solid adhesive of the present invention, its detailed structure, specific embodiments and other effects can be fully understood by referring to the description of the following drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1A The figure is a manufacturing flow chart of the electromagnetically activated moisture reactive solid adhesive of the present invention.

[0036] Figure 1B The chemical reaction formula of the electromagnetic activated moisture reactive solid adhesive manufacturing process of the present invention is shown in FIG.

[0037] Figure 2A The present invention is a flow chart of the production of the electromagnetically polarized activator used in the production of the electromagnetically activated moisture-reactive solid adhesive.

[0038] Figure 2B for Figure 2A Illustration of the chemical reactions that underlie the manufacturing process.

[0039] Figure 3A This is a solid-state crystalline chemical structure diagram of the electromagnetically activated moisture-reactive solid adhesive of the present invention before being electromagnetically polarized.

[0040] Figure 3B , Figure 3C for Figure 3A Schematic diagram of electromagnetically activated moisture-reactive solid adhesive being electromagnetically polarized to break the hydrogen bonds of polyurethane crystals and transform from a crystalline solid state to an amorphous liquid state.

[0041] Figure 4 Schematic diagram of the structure of silver nanowire.

[0042] Figure 5 Schematic diagram of the structure of carbon nanotubes.

[0043] 101: prepolymer, tackifier, additive and filler are mixed and heated;

[0044] 101A: prepolymer;

[0045] 102: Cooling;

[0046] 103: adding an electromagnetic polarization active agent;

[0047] 104: Mixed;

[0048] 105: adding diisocyanate;

[0049] 105A: diisocyanate;

[0050] 106: Heating;

[0051] 107: polymer polymerization;

[0052] 108: Catalyst;

[0053] 109: Vacuuming;

[0054] 110: unloading and packaging;

[0055] 201: coupling agent;

[0056] 202: Electron group regulator;

[0057] 203: solvent solution;

[0058] 204: resistance adjusting agent solution;

[0059] 205: Inorganic carrier;

[0060] 206: Mixing and stirring;

[0061] 207: Grafting modification of organic and inorganic substances;

[0062] 208: The surface of the carrier has a slight resistance;

[0063] 209: vacuum drying to evaporate the solvent;

[0064] 210: Fluidized bed drying and electrostatic coating;

[0065] 211: Electromagnetic polarization active agent. DETAILED DESCRIPTION

[0066] The electromagnetically activated moisture-reactive solid adhesive of the present invention can rapidly concentrate and disperse the charged structure of the electromagnetically polarized active agent by rapidly changing the positive and negative electric fields, thereby breaking the hydrogen bond crystal structure of the moisture-reactive solid adhesive to liquefy it and achieve adhesion. Its composition is described as follows:

[0067] The electromagnetic polarization moisture-reactive solid glue is composed of:

[0068] 1. Prepolymer: Also known as prepolymer, generally also called polyol, with a molecular weight of 200-10000, medium-long chain structure, so the physical properties are very poor. It is a substance formed by the initial polymerization of monomers. It is used in situations where it is difficult for monomers to be fully polymerized into polymers at one time, or to avoid the formation of voids and cracks in the polymer during processing and molding. It also refers to a polymer with a lower molecular weight whose degree of polymerization is between the monomer and the final polymer, usually referring to the polymer in the previous stage of preparing the final polymer.

[0069] The preferred prepolymers used in the present invention are as follows:

[0070] a) Polyester prepolymer (polyester polyol), its chemical formula is:

[0071]

[0072] Wherein, a and n are positive integers ranging from 1 to 99.

[0073] b) Polyether prepolymer (polyether polyol), its chemical formula is:

[0074]

[0075] Among them, n1 and n2 are positive integers ranging from 1 to 99.

[0076] c) Polytetrahydrofuran type prepolymer (Polytetrmethylene ether glycol polyol), its chemical formula is:

[0077]

[0078] Here, n is a positive integer ranging from 1 to 99.

[0079] d) Polycaprolactone prepolymer (Polycaprolactone polyol), the chemical formula of which is:

[0080]

[0081] Wherein, n and m are positive integers ranging from 1 to 99.

[0082] e) Polycarbonate prepolymer (Polycarbonate polyol), the chemical formula of which is:

[0083]

[0084] Here, n is a positive integer ranging from 1 to 99.

[0085] f) Polyhydroxyl-terminated acrylate prepolymer (Polyhydroxyl-terminated acrylate polyol), the chemical formula of which is:

[0086]

[0087] Wherein, n is a positive integer of 1 to 99, R is an alkane-hydrogen compound, and its chemical formula is CnH 2n+2 or CnH 2n , where n ranges from 1 to 99.

[0088] g) Polyhydroxyl-terminated polybutadiene prepolymer, the chemical formula of which is:

[0089]

[0090] Here, n is a positive integer ranging from 1 to 99.

[0091] h) Polyhydroxyl-terminated epoxy prepolymer, the chemical formula of which is:

[0092]

[0093] Here, n is a positive integer ranging from 1 to 99.

[0094] The above prepolymers have a common feature, which can be seen from their chemical formulas, that is, their terminal groups are hydroxyl groups (Hydroxy bond-OH). The prepolymers can be mixed to adjust the physical properties of the solid adhesive.

[0095] 2. Diisocyanate curing agent: It is highly toxic, but as mentioned above, the molecular weight of polyol is 200-10000 medium-long chain structure. The NCO functional groups at both ends of diisocyanate will react with the hydroxyl (OH) functional groups at both ends of polyol to generate amino acid formate. At this time, a polymerization reaction will occur, which will increase the molecular weight of the prepolymer from 200-10000 to 100,000-400,000 or more, and the physical properties will be greatly improved. Carbamate is a stable, environmentally friendly and non-toxic compound. This is due to the fact that diisocyanate and polyol prepolymers are non-toxic after the polymerization reaction.

[0096] The preferred diisocyanates used in the present invention are as follows:

[0097] a) Diphenylmethane diisocyanate, its chemical formula is:

[0098]

[0099] b) Toluene diisocyanate, its chemical formula is:

[0100]

[0101] c) 1,5-Naphthalene diisocyanate, whose chemical formula is:

[0102]

[0103] d) Isophorone diisocyanate, whose chemical formula is:

[0104]

[0105] e) Hydrogenated diphenylmethane diisocyanate (4,4'-dicyclohexylmthane diisocyanate), the chemical formula of which is:

[0106]

[0107] 3. Tackifier: It is used to increase the surface wettability of the adhesive to the adhered substrate. The tackifier will reduce the cohesive force of the polymer, increase the fluidity, and penetrate into the surface pores of the adhered substrate to increase the contact surface area and wettability, without basically changing other physical properties. The preferred ones have low acid value, good miscibility, low melting point, water resistance, ethanol resistance and chemical resistance.

[0108] The preferred tackifiers used in the present invention are as follows:

[0109] a) Abietic resin, its chemical formula is:

[0110]

[0111] b) Terpene resin, the chemical formula of which is:

[0112]

[0113] Here, n is a positive integer ranging from 1 to 99.

[0114] c) Hydrocarbon resin (HCR): It is a thermoplastic resin produced by pre-treatment, polymerization, distillation and other processes of C5, C6, C9 and other fractions produced by petroleum production. It is also divided into many types according to different raw materials. There is no single structural formula. The better ones are:

[0115] ①C5 Petroleum resin.

[0116] ②C6 petroleum resin.

[0117] ③C9 petroleum resin.

[0118] 4. Auxiliary: Based on monomers, polymers, oligomers and surfactants, it has the effects of defoaming, preventing precipitation, increasing viscosity, improving product appearance, improving anti-sagging, coloring, reducing viscosity, improving gloss, certainty and balance (the structure of auxiliary agents is confidential to each manufacturer and no structural formula is available). For example, it can be: a) defoaming agent, b) leveling agent, c) anticratering agent, d) rheological agent, e) thixotropy agent.

[0119] 5. Filler: Also known as filler or extender, it is used to improve the working performance and product strength, etc. It can be: a) talcum powder, b) calcium carbonate, c) kaolin, etc.

[0120] 6. Electromagnetically polarized active agent carrier: refers to a carrier that can be used to carry the electromagnetically polarized active agent in the present invention, which is preferably the following powdered or granular compounds: a) quartz, b) zirconium oxide, c) silicon carbide, d) zinc oxide, e) calcium oxide, f) magnesium oxide, g) copper oxide, h) calcium carbonate, i) mica, j) iron oxide, k) alumina, l) carbon, m) graphite and its isomers, n) solid polymer microspheres, o) hollow polymer microspheres.

[0121] 7. Resistance adjuster: It is a conductive compound or polymer used to adjust the trace resistance on the surface of the carrier, including:

[0122] a) Polystyrene sulfonate (poly(3,4-ethylenedioxythiophene)): Polythiophene (polythiophene), its chemical formula is:

[0123]

[0124] Here, m is a positive integer ranging from 1 to 99.

[0125] b) Silver nanowire: Its structure is as follows Figure 4 As shown;

[0126] c) Carbon nanotube: Its structure is as follows Figure 5 As shown;

[0127] d) Graphene: Its structure is as follows:

[0128]

[0129] e) Octylphenol polyoxyethylene ether {[(Tetramethylbutyl)phenoxy]ethoxy}ethanol, the chemical formula of which is:

[0130]

[0131] f) Monoalkyl ether phosphate: Its chemical formula is:

[0132]

[0133] Here, n is a positive integer ranging from 1 to 99.

[0134] 8. Catalyst: used to accelerate polymerization reaction, including:

[0135] a) Dibutyltin dilaurate: Its chemical formula is:

[0136]

[0137] b) N,N-Dimethyltrimethylenediamine: Its chemical formula is:

[0138]

[0139] 9. Coupling agent: It is an additive used in plastic compounding to improve the interface performance between synthetic resin and inorganic filler or reinforcing material, also known as surface modifier. It can reduce the viscosity of synthetic resin melt during plastic processing, improve the dispersion of filler to improve processing performance, and thus make the product have good surface quality and mechanical, thermal and electrical properties. Coupling agent generally consists of two parts, one part is inorganic affinity group, which can react with inorganic filler or reinforcing material, and the other part is organic affinity group, which can react with synthetic resin. Contains:

[0140] a) Vinyltrimethoxysilane (Dibutyltin dilaurate), the chemical formula is as follows:

[0141]

[0142] b) Vinyltriethoxy silane, the chemical formula is as follows:

[0143]

[0144] c) 3-isocyanatopropyl(trimethoxy)silane, the chemical formula is as follows:

[0145]

[0146] d) (3-Aminopropyl)triethoxysilane, the chemical formula is as follows:

[0147]

[0148] e) (3-Aminopropyl) trimethoxysilane [(3-Aminopropyl) trimethoxysilane], the chemical formula is as follows:

[0149]

[0150] The manufacturing process of the electromagnetic polarized moisture reactive solid adhesive of the present invention is as follows: Figure 1A and Figure 1B As shown:

[0151] 1. As Figure 1A and Figure 1B As shown, first, prepolymer 101A (10-95%), tackifier (1-30%), auxiliary agent (0.01-10%), filler (1-30%), one or more, are mixed and heated to 100°C-150°C, and dried and dehydrated under vacuum at 650-760 mmHg for 30 minutes-4 hours (prepolymer tackifier auxiliary agent filler is mixed and heated 101) to obtain a prepolymer without trace water molecules to prevent diisocyanate from reacting with water molecules with higher reaction activity with hydroxyl groups first. After the water molecules have reacted, they will react with the polyol prepolymer with lower reaction activity with hydroxyl groups, so as to avoid incomplete polymerization of the polyol prepolymer.

[0152] 2. The temperature is lowered to below 70°C (cooling 102) and an electromagnetic polarization activator (its manufacture is described below) is added. After mixing under a nitrogen atmosphere, diisocyanate is slowly added. The temperature is raised 106 to 80-150°C to start a 1.5-4 hour polymer polymerization reaction 107, and the terminal isocyanate content is controlled to be 0.1-25% by the molar number and equivalent number of isocyanate groups (hydroxyl groups); for example: when (NCO / OH)>1, NCO functional groups are easily left at both ends of the polymer after the polymer polymerization reaction, and the polymer with NCO functional groups left at both ends will react with water molecules in the air to undergo moisture curing cross-linking reaction.

[0153] 3. Add catalyst 108 under nitrogen atmosphere.

[0154] 4. After adding the catalyst 108, vacuum is applied to 650-760 mmHg (vacuum 109) to remove air bubbles.

[0155] 5. Unload into an aluminum foil package (unloading package 110) in a nitrogen atmosphere and seal.

[0156] The electromagnetically activated moisture-reactive solid adhesive of the present invention is prepared by the following method for preparing the electromagnetically polarized activator used in its preparation (please refer to Figure 2A and Figure 2B ):

[0157] 1. First, one or more of the silane coupling agent 201 and the resistance adjusting agent 202 are dissolved in a solvent (solvent solution 203) such as acetone, butanone, toluene, ethanol, ethyl acetate, dimethylacetamide, etc., to obtain a resistance adjusting agent solution 204 with a solid content of (0.1-30%).

[0158] 2. Pour the carrier (inorganic carrier 205) in the required amount into the above-mentioned coupling agent 201 and resistance adjusting agent 202 solution and mix and stir (mix and stir 206) for 2-5 hours to make the carrier surface undergo organic and inorganic coupling grafting modification (organic and inorganic grafting modification 207) and adjust the trace resistance on the carrier surface to 1mΩ·cm~1GΩ·cm (carrier surface with trace resistance 208).

[0159] 3. The above solution is vacuum dried (vacuum drying and volatile solvent 209) to completely evaporate the solvent, leaving a solid powder product of the organic molecule-coated carrier.

[0160] 4. The solid powder product is passed through a fluidized bed dryer and a high-voltage electron beam gun to make the surface of the solid powder of the organic molecule-coated carrier electrostatically charged (fluidized bed drying and electrostatic coating 210) to obtain an electromagnetic polarized activator 211 product.

[0161] The electromagnetically activated moisture-reactive solid adhesive of the present invention can rapidly concentrate and disperse the charged structure of the electromagnetically polarized active agent by rapidly changing the positive electric field and the negative electric field, thereby breaking the hydrogen bond crystal structure of the moisture-reactive solid adhesive to liquefy it and achieve adhesion.

[0162] In summary, the electromagnetically activated moisture-reactive solid adhesive of the present invention has not been seen in any publications, and there are no similar products on the market, so it is novel. In addition, the unique features and functions of the present invention are far beyond the existing ones, so it is indeed more progressive than the existing ones, and it complies with the provisions of the Patent Law of my country on the application of invention patents, so a patent application is filed in accordance with the law.

[0163] However, what is described above is only a preferred embodiment of the present invention, and should not be used to limit the scope of implementation of the present invention. That is, any simple equivalent changes and modifications made according to the scope of the patent application of the present invention and the content of the specification should still fall within the scope covered by the patent of the present invention.

Claims

1. An electromagnetically activated moisture-reactive solid adhesive, characterized in that: The manufacturing method thereof comprises the following steps: (1) mixing 10-95% of a prepolymer, 1-30% of a tackifier, 0.01-10% of an auxiliary, and 1-30% of a filler, or one or more formulations, heating the mixture to 100° C. to 150° C., and drying and dehydrating the mixture under a vacuum of 650 to 760 mmHg for 30 minutes to 4 hours to obtain a prepolymer composition liquid; (2) cooling the obtained prepolymer combination liquid to below 70° C., adding an electromagnetic polarization activator (EMPA), mixing evenly under a nitrogen atmosphere, slowly adding a diisocyanate curing agent (Diisocyanate) under a nitrogen atmosphere, heating to 80-150° C., allowing the prepolymer mixture to undergo a polymer polymerization reaction for 1.5-4 hours, and controlling the terminal isocyanate content to be 0.1-25%; (3) adding a catalyst under the nitrogen atmosphere to accelerate the polymerization reaction; (4) In a vacuum environment of 650-760 mmHg, the nitrogen in the reaction chamber is evacuated to remove bubbles from the polymerization product to obtain a solid adhesive; (5) Unload the material into a nitrogen-protected aluminum foil package and seal it to obtain the product; The method for producing the electromagnetic polarization active agent comprises the following steps: (1) dissolving one or more of a silane coupling agent and a resistance adjusting agent in acetone, butanone, toluene, ethanol, ethyl acetate or dimethylacetamide to obtain a resistance adjusting agent solution having a solid content of (0.1-30%); (2) Pour the required amount of the carrier into the above-mentioned coupling agent and resistance adjusting agent solution and mix and stir for 2-5 hours to make the surface of the carrier undergo organic and inorganic coupling grafting modification and adjust the trace resistance of the carrier surface to 1 mΩ·cm~1 GΩ·cm; (3) vacuum drying the solution to completely evaporate the solvent, leaving a solid powder product of the organic molecule-coated carrier; (4) The solid powder product is passed through a fluidized bed dryer and a high-voltage electron beam gun to make the surface of the solid powder of the organic molecule-coated carrier electrostatically charged, thereby obtaining an electromagnetically polarized active agent product.

2. The electromagnetically activated moisture reactive solid adhesive according to claim 1, characterized in that: The prepolymer is a substance formed by preliminary polymerization of a monomer, and the terminal group of the prepolymer is a hydroxyl bond (Hydroxy bond-OH).

3. The electromagnetically activated moisture reactive solid adhesive according to claim 2, characterized in that: The prepolymer is (a) polyester prepolymer (polyester polyol), (b) polyether prepolymer (polyether polyol), (c) polytetrahydrofuran prepolymer (polytetrmethylene ether glycol polyol), (d) polycaprolactone prepolymer (polycaprolactone polyol), (e) polycarbonate prepolymer (polycarbonate polyol), (f) polyhydroxyl-terminated acrylate prepolymer (polyhydroxyl-terminated acrylate polyol), (g) polyhydroxyl-terminated polybutadiene prepolymer (polyhydroxyl-terminated The prepolymer is a mixture of one or more of (i) polybutadiene and (ii) polyhydroxyl-terminated epoxy.

4. The electromagnetically activated moisture reactive solid adhesive according to claim 1, wherein: The curing agent is an isocyanate curing agent.

5. The electromagnetically activated moisture reactive solid adhesive according to claim 4, characterized in that: The curing agent is one or more of: a) diphenylmethane diisocyanate; b) toluene diisocyanate; c) 1,5-naphthalene diisocyanate; d) isophorone diisocyanate; and e) hydrogenated diphenylmethane diisocyanate.

6. The electromagnetically activated moisture reactive solid adhesive according to claim 1, characterized in that: The tackifier is one or more of: a) abietic resin; b) terpene resin; c) hydrocarbon resin (HCR).

7. The electromagnetically activated moisture reactive solid adhesive according to claim 1, characterized in that: The auxiliary agent is one or more of: a) an antifoaming agent, b) a leveling agent, c) an anticratering agent, d) a dilatant thickener, and e) a thixotropy agent.

8. The electromagnetically activated moisture reactive solid adhesive according to claim 1, wherein: The filler is at least one of a) talcum powder, b) calcium carbonate or c) kaolin.

9. The electromagnetically activated moisture reactive solid adhesive according to claim 1, wherein: The catalyst is at least one of: a) dibutyltin dilaurate; and b) N,N-dimethyltrimethylenediamine.

10. The electromagnetically activated moisture reactive solid adhesive according to claim 1, wherein: The electromagnetically polarized active agent carrier is the following powdery or granular compound: a) quartz, b) zirconium oxide, c) silicon carbide, d) zinc oxide, e) calcium oxide, f) magnesium oxide, g) copper oxide, h) calcium carbonate, i) mica, j) iron oxide, k) alumina, l) carbon, m) graphite and its isomers, n) solid polymer microspheres, and o) hollow polymer microspheres.

11. The electromagnetically activated moisture reactive solid adhesive according to claim 1, wherein: The resistance adjuster is a conductive polymer used to adjust the trace resistance on the surface of the carrier, including: a) polystyrene sulfonate (poly(3,4-ethylenedioxythiophene)); polythiophene; b) silver nanowire; c) carbon nanotube; d) graphene; e) octylphenol polyoxyethylene ether {[(Tetramethylbutyl)phenoxy] f) at least one of monoalkyl ether phosphate.

12. The electromagnetically activated moisture reactive solid adhesive according to claim 1, characterized in that: The coupling agents are: a) vinyl trimethoxy silane (Dibutyltin dilaurate), b) vinyl triethoxy silane (Vinyltriethoxy silane), c) isocyanate propyl trimethoxy silane [3-isocyanatopropyl(trimethoxy)silane], d)(3-aminopropyl)triethoxysilane [(3-Aminopropyl)triethoxysilane]), e) (3-Aminopropyl)trimethoxysilane [(3-Aminopropyl)trimethoxysilane].